Pengaruh Struktur Modal dan Profitabilitas Terhadap PPh Terutang Badan dengan Tax Avoidance sebagai Variabel Moderasi - Ghefira Nur Azizah; Rahmat Mulyana Dali; Rasiman . (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Corporate Income Tax is one of the major sources of government revenue that supports national development. The amount of Corporate Income Tax Payable is influenced by various internal corporate factors, including capital structure and profitability. However, previous studies have produced inconsistent findings regarding the effects of these variables on Corporate Income Tax Payable, indicating the need for further investigation by incorporating tax avoidance as a moderating variable. This study aims to analyze the effect of capital structure and profitability on Corporate Income Tax Payable and to examine the moderating role of tax avoidance in the relationship between capital structure, profitability, and Corporate Income Tax Payable. This study employed a quantitative approach with a causal associative research design. The population consisted of consumer non-cyclicals companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The sample was selected using purposive sampling techniques based on predetermined criteria. Secondary data were obtained from annual financial reports, and data collection was conducted through documentation techniques. Data analysis was performed using panel data regression and Moderated Regression Analysis (MRA). The results indicate that capital structure and profitability have a positive and significant effect on Corporate Income Tax Payable. Tax avoidance does not have a significant effect on Corporate Income Tax Payable. Furthermore, tax avoidance is unable to moderate the relationship between capital structure and Corporate Income Tax Payable, nor the relationship between profitability and Corporate Income Tax Payable. Capital structure and profitability are significant determinants of Corporate Income Tax Payable, whereas tax avoidance does not function as a moderating variable. These findings imply that companies should pay greater attention to profitability and capital structure management in tax planning strategies, while tax avoidance has not been proven to strengthen or weaken the influence of these variables on Corporate Income Tax Payable.